Recent Advances in the Synthesis of High Boron-Loaded Nucleic Acids for BNCT - Novopashina, Darya Sergeevna; Vorobyeva, Mariya Alexandrovna; Venyaminova, Alya (Frontiers in Chemistry, 2021)
Boron clusters attract considerable attention as promising therapeutic tools for boron neutron capture therapy (BNCT). They combine high boron content with high chemical and biological stability, biorthogonality, and low toxicity. The development of oligonucleotide-based constructs and nucleic acid-like molecules, such as oligomeric phosphate diesters, bearing one or multiple boron clusters permits to create potential high boron-loaded agents for BNCT with good bioavailability, specifically interacting with nucleic acids inside the cell. Here, we shortly review the strategies and solutions in the design of oligonucleotide conjugates with boron clusters in light of the requirements for effective BNCT and future prospects of their practical use.